Accountability and corruption : political institutions matter - Lederman, Daniel 1968- (Policy research working paper, 2001)
The results of a cross-country empirical analysis suggests that political institutions are extremely important in determining the prevalence of corruption: democracy, parliamentary systems, political stability, and freedom of the press are all associated with lower corruption